Comparative genomic hybridization and transcriptome analysis with a pan‐genome microarray reveal distinctions between JP2 and non‐JP2 genotypes of Aggregatibacter actinomycetemcomitans. (12th October 2012) - Huang, Y.; Kittichotirat, W.; Mayer, M.P.A.; Hall, R.; Bumgarner, R.; Chen, C.
Summary It was postulated that the highly virulent JP2 genotype of Aggregatibacter actinomycetemcomitans may possess a constellation of distinct virulence determinants not found in non‐JP2 genotypes. This study compared the genome content and the transcriptome of the serotype b JP2 genotype and the closely related serotype b non‐JP2 genotype of A. actinomycetemcomitans. A custom‐designed pan‐genomic microarray of A. actinomycetemcomitans was constructed and validated against a panel of 11 sequenced reference strains. The microarray was subsequently used for comparative genomic hybridization of serotype b strains of JP2 (six strains) and non‐JP2 (six strains) genotypes, and for transcriptome analysis of strains of JP2 (three strains) and non‐JP2 (two strains). Two JP2‐specific and two non‐JP2‐specific genomic islands were identified. In one instance, distinct genomic islands were found to be inserted into the same locus among strains of different genotypes. Transcriptome analysis identified five operons, including the leukotoxin operon, to have at least two genes with an expression ratio of 2 or greater between genotypes. Two of the differentially expressed operons were members of the membrane‐bound nitrate reductase system (nap operon) and the Tol‐Pal system of gram‐negative bacterial species. This study is the first to demonstrate the differences in the full genome content and gene expression between A. actinomycetemcomitans strains of JP2 and non‐JP2 genotypes. The information is essential for designing hypothesis‐driven experiments to examine the pathogenic mechanisms of A. actinomycetemcomitans.